Thyroid Function Tests Abnormalities in Patients on Thrice Weekly Hemodialysis - SHAHID ANWAR, ALVINA ZANIB, (Journal of Fatima Jinnah Medical University, 2018)
Background: The diagnosis of thyroid disorder is rather difficult in patients with chronic kidney disease on maintenance hemo-dialysis (HD) due to their overlapping clinical features. The overlooked thyroid problems can be a cause of increased morbidity and mortality among end-stage renal disease (ESRD) uremic patients. Both hypothyroidism and eu-thyroid sick syndrome are least addressed precipitating factors of all-cause and cardiovascular mortality in uremic patients. This study intends to fractionate the patients with thyroid dysfunction on maintenance hemo-dialysis. Patients and Methods: Seventy patients of ESRD booked for thrice weekly HD, 3-4 hours per sessions in Dialysis center of Sir Ganga Ram Hospital, Lahore underwent blood sampling for measurement of serum free T3, free T4 & TSH during their active HD session. All patients were categorized to overt hypothyroidism, overt hyperthyroidism, subclinical hypothyroidism, subclinical hyperthyroidism and euthyroid sick syndrome and its subtypes according to their laboratory values. Results: Male to female ratio was 1.9:1, with mean age of 47 years. Euthyroid status, hypothyroidism and euthyroid sick syndrome were observed in 32%, 12.9% and 57.1% patients respectively. Conclusion: It is concluded that most of HD patients are either suffering from euthyroid sick syndrome or hypothyroidism. As euthyroid sick syndrome can be a causative factor for sudden cardiac death, regular assessment of thyroid function tests in patients on maintenance HD is recommended to determine cardiac risk of dialysis patients.